RENCANA PENGEMBANGAN SEKOLAH - Rodiah Mukhtar (Manajer Pendididikan, 2015)
The purpose of this study is to describe the school development plan at senior high school Number 1 Lubuklinggau. This study uses descriptive qualitative method. The subjects of this study are the school principal, the vice of the school principals, the teachers, the staff, students’ parent, and the students. The data were collected by means of interview, observation, and documentation. Afterwards, the data collected were analyzed by using qualitative descriptive technique. The result of this study shows that in general the school development plan at senior high school number 8 Lubuklinggau has not yet fulfilled the standard operating procedure.Keyword: school development, plan.